The association of minimum wage change on child nutritional status in LMICs: A quasi-experimental multi-country study*. Issue 9 (2nd September 2018) - Ponce, Ninez; Shimkhada, Riti; Raub, Amy; Daoud, Adel; Nandi, Arijit; Richter, Linda; Heymann, Jody
ABSTRACT: There is recognition that social protection policies such as raising the minimum wage can favourably impact health, but little evidence links minimum wage increases to child health outcomes. We used multi-year data (2003–2012) on national minimum wages linked to individual-level data from the Demographic and Health Surveys (DHS) from 23 low- and middle-income countries (LMICs) that had least two DHS surveys to establish pre- and post-observation periods. Over a pre- and post-interval ranging from 4 to 8 years, we examined minimum wage growth and four nutritional status outcomes among children under 5 years: stunting, wasting, underweight, and anthropometric failure. Using a differences-in-differences framework with country and time-fixed effects, a 10% increase in minimum wage growth over time was associated with a 0.5 percentage point decline in stunting (−0.054, 95% CI (−0.084, −0.025)), and a 0.3 percentage point decline in failure (−0.031, 95% CI (−0.057, −0.005)). We did not observe statistically significant associations between minimum wage growth and underweight or wasting. We found similar results for the poorest households working in non-agricultural and non-professional jobs, where minimum wage growth may have the most leverage. Modest increases in minimum wage over a 4- to 8-year period might be effective in reducing child undernutrition in LMICs.